Science Fiction in Translation
XVII, 359 p. 3 illus.
Keywords: Science Fiction in Translation: Perspectives on the Global Theory and Practice of Translation focuses on the process of translation and its implications. The volume explores the translation of works of science fiction (SF) from one language to another and the translation of SF tropes, terms, and ideas of SF theory into cultures outside the West. Providing a comprehensive examination of the state of translation into English, the essays consider how representative the body of translated work of SF is from the source language/culture. It also considers the social, political, and economic choices in selecting a work to translate. The book illustrates the dramatic growth both in SF production outside the Anglosphere, the translation of works from other languages into English, and the practice of translating English-language SF into other languages. Altogether, the essays map the theory, practice, and business of SF translation around the world.